HPLC-DAD-ESI-MS profile, antibacterial activity, and modulation of the activity of antibiotics by Carica papaya L. against Escherichia coli serotypes - Cícera Natalia Figueiredo Leite Gondim; Denise Aline Casimiro Bezerra; Nadghia Figueiredo Leite Sampaio; Maria Anésia Sousa de.Alencar; Roger Henrique Sousa da.Costa; Lucas Silva Abreu; Joanda Paolla Raimundo.e.Silva; Francisco Nascimento Pereira Junior; Josean Fechine Tavares; Marcelo Sobral da Silva; Jaime Ribeiro-Filho; Henrique Douglas Melo Coutinho (Elsevier, 2022)
Background: Diarrhea is currently the second leading cause of death among children under five years old in the world and therefore, remains a global public health problem. Considering that most cases of diarrhea are due to gastrointestinal infections, and medicinal plants have been traditionally used to treat such conditions, this work aimed to evaluate the chemical composition, antibacterial activity, and antibiotic-enhancing properties of C. papaya against Escherichia coli, EPEC (Enteropathogenic E. coli), and ETEC (Enterotoxigenic E. coli) serotypes.Methods: The chemical profile of the aqueous extract obtained from C. papaya leaves was determined by HPLC-DAD-ESI-MS. The antibacterial and antibiotic-enhancing activities were evaluated through the determination of the MIC, following the microdilution method.Results: A total of 17 compounds were identified by HPLC-DAD-ESI-MS. However, the extract of C. papaya did not present an intrinsic antibacterial effect, in addition to showing no modulatory effect when associated with antibiotics.Conclusions: Despite the presence of bioactive compounds, the aqueous extract C. papaya does not present antibacterial or antibiotic-enhancing effects against the ETEC and EPEC strains of E. coli. Nevertheless, further research is required to determine if its isolated components are potential drug candidates for the therapy of infections caused by these strains.